Decision Support System for Supplier Selection on Time Concept with AHP and SAW Method - Warih Dwi Cahyo; Wahyu Ari Wibowo; Suwarno Suwarno; Rizki ripai (Kresnamedia Publisher, 2022)
Seeing the rapid development of global business causes companies to compete as the best to meet global market demands. In the current era of globalization, technological development is beneficial for human life. All human activities today can be done quickly and easily using a computer. Decision Support System is a computer-based system that assists decision-making in utilizing specific data and models to solve various unstructured problems. Decision makers in selecting the best supplier for Time Concept are still having difficulties, and this is because there are no appropriate criteria and weights. Making a decision support system is expected to help solve the problems in Time Concept. Moreover, it can provide benefits or convenience for Time Concept when selecting the best supplier. The author uses the method of Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW). According to the system test results, the Consistency Ratio (CR) calculation value is 0.0752. The comparison assessment is considered CONSISTENT if the Consistency Ratio (CR) value is not greater than 0.1000. So that the comparison of the criteria does not need to be recalculated because it is CONSISTENT.